ANALISIS BUDAYA ORGANISASI, KEPEMIMPINAN, DAN MOTIVASI TERHADAP KINERJA PEGAWAI PT. BANK PANIN TBK CABANG PANGKALPINANG - Bambang Bernanthos (Jurnal Manajemen FE-UB, 2013)
This research is a quantitative study using sun,ey research methods to the population. Respondents data were tested using the test of assumptions of classical instruments. analyzed using descriptive statistics and inferential statistics with multiple linear regression analysis. Multiple correlation analysis and determination analysis used in order to see the relationship and influence of independent variables to the dependent variable. Independent variables in this study is organizational culture, leadership, and motivation, while the dependent variable is performance. This research tests the hypothesis using simultaneous and partial. Based on the results of research and the discussion shows there is a significant variable influences organizational culture, leadership, and motivation integratedly on the perforrnance of employees of PT. Bank Panin Tbk Pangkalpinang Branch, it can be seen from the results of I: test with the significant/probability (0.000) <a (0.05) and Fhitung (9.274)> Frabel (2.883), these results shows that integratedly the organizational culture, leadership, and motivation have a signific effect on performance. Multiple regression equation was Y = 11.916 + 0.576 X1 + 0.086 0.078 X3. The value R = 0.863, which means the influence of organizational culture, leaders p and motivation integraledly have a very strong relationship to performance. Determination coefficient = 0.745, this value can be defined that 74.5% of performance vanables •an be explained by organizational culture, leadership, and motivation integratedly, the remaming 25.5% of the other variables not included in the research.